Initiation of immunotherapy with activated natural killer cells and anti-GD2 antibody dinutuximab prior to resection of primary neuroblastoma prolongs survival in mice. Issue 2 (18th December 2020) - Zobel, Michael John; Zamora, Abigail K; Wu, Hong-wei; Sun, Jianping; Lascano, Danny; Malvar, Jemily; Wang, Larry; Sheard, Michael A; Seeger, Robert C; Kim, Eugene S
Abstract : Background: Immunotherapy with anti-disialoganglioside dinutuximab has improved survival for children with high-risk neuroblastoma (NB) when given after induction chemotherapy and surgery. However, disease recurrence and resistance persist. Dinutuximab efficacy has not been evaluated when initiated before primary tumor removal. Using a surgical mouse model of human NB, we examined if initiating dinutuximab plus ex vivo-activated natural killer (aNK) cells before resection of the primary tumor improves survival. Methods: In vitro, human NB cells (SMS-KCNR-Fluc, CHLA-255-Fluc) were treated with dinutuximab and/or aNK cells and cytotoxicity was measured. In vivo, NB cells (SMS-KCNR-Fluc, CHLA-255-Fluc, or COG-N-415x PDX) were injected into the kidney of NOD-scid gamma mice. Mice received eight intravenous infusions of aNK cells plus dinutuximab beginning either 12 days before or 2 days after resection of primary tumors. Tumors in control mice were treated by resection alone or with immunotherapy alone. Disease was quantified by bioluminescent imaging and survival was monitored. aNK cell infiltration into primary tumors was quantified by flow cytometry and immunohistochemistry at varying timepoints. Results: In vitro, aNK cells and dinutuximab were more cytotoxic than either treatment alone. In vivo, treatment with aNK cells plus dinutuximab prior to resection of the primary tumor was most effective in limiting metastatic disease and prolonging survival. aNK cell infiltration into xenograft tumors was observed after 1 day and peaked at 5 days following injection. Conclusion: Dinutuximab plus aNK cell immunotherapy initiated before resection of primary tumors decreases disease burden and prolongs survival in an experimental mouse model of NB. These findings support the clinical investigation of this treatment strategy during induction therapy in patients with high-risk NB.